Human Cytomegalovirus Interleukin 10 Homologs: Facing the Immune System - Poole, Emma; Neves, Tainan Cerqueira; Oliveira, Martha Trindade; Sinclair, John; da Silva, Maria Cristina Carlan (Frontiers in Cellular and Infection Microbiology, 2020)
Human Cytomegalovirus (HCMV) can cause a variety of health disorders that can lead to death in immunocompromised individuals and neonates. The HCMV lifecycle comprises both a lytic (productive) and a latent (non-productive) phase. HCMV lytic infection occurs in a wide range of terminally differentiated cell types. HCMV latency has been less well studied, but one characterised site of latency is in precursor cells of the myeloid lineage. All known viral genes are expressed during a lytic infection and a subset of these are also transcribed during latency. The UL111A gene which encodes the viral IL-10, a homologue of the human IL-10, is one of these genes. During infection, different transcript isoforms of UL111A are generated by alternative splicing. The most studied of the UL111A isoforms are cmvIL-10 (also termed the 'A' transcript) and LAcmvIL-10 (also termed the 'B' transcript), the latter being a well characterised latency associated transcript. Both isoforms can downregulate MHC class II, however they differ in a number of other immunomodulatory properties, such as the ability to bind the IL10 receptor and induce signalling through STAT3. There are also a number of other isoforms which have been identified which are expressed by differential splicing during lytic infection termed C, D, E, F and G, although these have been less extensively studied. HCMV uses the viral IL-10 proteins to manipulate the immune system during lytic and latent phases of infection. In this review, we will discuss the literature on the viral IL-10 transcripts identified to date, their encoded proteins and the structures of these proteins as well as the functional properties of all the different isoforms of viral IL-10.